2019
DOI: 10.1371/journal.pone.0221695
|View full text |Cite
|
Sign up to set email alerts
|

Influence of leg length inequalities on pelvis and spine in patients with total hip arthroplasty

Abstract: Background Leg length inequalities (LLIs) are a common finding in patients with a total hip arthroplasty (THA). Therefore, we compared the effects of simulated LLIs in patients with total hip arthroplasty (THA) with a matched control group. Research question Do LLIs lead to different effects on the musculoskeletal apparatus of patients with a THA then in a control group? Methods In 99 patients with a THA the effects of simulated LLIs were com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 36 publications
0
14
2
2
Order By: Relevance
“…LLD is a common complication of THA, which may cause short-term hip pain and discomfort that result in lameness, compensatory pelvic tilt or scoliosis, and even aseptic loosening of the prosthesis in the long term [ 4 , 11 ]. Previous literature has shown that it is clinically acceptable to have unequal leg length of less than 10 mm in terms of imaging [ 1 ]. In our study, more than 1/4 patients had LLD after bilateral hip replacement, even 18 of them were larger than 10 mm.…”
Section: Discussionmentioning
confidence: 99%
“…LLD is a common complication of THA, which may cause short-term hip pain and discomfort that result in lameness, compensatory pelvic tilt or scoliosis, and even aseptic loosening of the prosthesis in the long term [ 4 , 11 ]. Previous literature has shown that it is clinically acceptable to have unequal leg length of less than 10 mm in terms of imaging [ 1 ]. In our study, more than 1/4 patients had LLD after bilateral hip replacement, even 18 of them were larger than 10 mm.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that differences in limb lengths can introduce spinopelvic obliquity as a compensatory mechanism [14]. Total hip arthroplasty resulting in a limb length discrepancy can invite rotational compensatory changes in the spinopelvic complex [15]. The prolonged consequences of these mechanisms are commonly sacroiliac [16] and back pain [17].…”
Section: Discussionmentioning
confidence: 99%
“…In order to achieve optimum measurement of the back surface, for each test person six anatomical landmarks (light-reflecting markers of 1 cm diameter) were necessary. The ABW-BodyMapper has already been used successfully in studies to determine representative standard values for young men (18-35 years) [32] and middle-aged men [41][42][43][44][45][46][47][48][49][50] [33] as well as women (21-30 years) [59]. Formula or algorithm used to calculate the evaluation parameters are published by Ohlendorf et al [33].…”
Section: Measurement Systemmentioning
confidence: 99%
“…The clear benefit to a 2 dimensional photography [46] or video analysis [47,48] is the depth information calculated from the projected lines onto a curvature. With progress in image reconstruction algorithms, surface parameters of the upper body can be calculated [32,34,41,49]. Obviously, it cannot measure below the surface, therefore a quantification of spinal parameters is not possible.…”
Section: Introductionmentioning
confidence: 99%